Checklist of Basidiomycetous fungi of Bangladesh - Shamsi, Shamim; Alam, Syed Arman (Bioresearch Communications, 2025)
A total of 261 species of Basidiomycetous fungi under 49 families in Bangladesh from 1952 till date are enlisted. The alphabetical checklist of the genera is provided herewith. Further updates will be added to the subsequent versions of the publication. Bioresearch Commu. 11(2): 1801-1810, 2025 (July)